Gender, Education, and Access to Quality Employment: Analysis of the Situation of Women in Indonesia in the Digital Economic Era - Nur Rahmah; Edy Wiranto; Muhammad Syahrul Hidayat; Yanti Mulia Roza; An Ras Try Astuti (GoAcademica Research & Publishing, 2023)
The digital economy's expansion in Indonesia has substantially influenced the country's access to high-quality employment opportunities. Nonetheless, the gender gap in work possibilities remains a severe problem in Indonesia, despite the enormous increases in the availability of quality employment prospects. This article studies Indonesian women's condition in the digital economy era, with a focus on the relationship between gender, education, and access to quality employment prospects. The essay also examines the situation of Indonesian women in the past. This investigation takes a qualitative approach and makes use of descriptive research tools. The study's findings indicate that despite a rise in employment opportunities due to the digital economy, women continue to need help gaining access to quality employment, particularly in fields still predominately held by men. Education is critical in boosting the number of women with access to high-quality work opportunities.